Compound odontoma with unususal number of denticles- a case report - Singh, Vivek; Singh, Jasmeet (Journal of Chitwan Medical College, 2020)
The term odontoma refers to hamartomatous lesions (malformations) rather than true neoplasms. They are the most common odontogenic tumour of jaws. They are slow growing in nature. Missing permanent tooth or retained deciduous tooth brings the patient to the clinician usually during second decade of life. Two types of odontomas has been described: complex and compound. The compound type is more common and frequently found in the anterior maxilla. A 15-year-old male patient reported to department Oral and Maxillofacial Surgery, with missing permanent right central and lateral incisor with retained deciduous in place. Intraoral radiographs were done and multiple small denticles were seen. A total of 39 denticles of various sizes were enucleated from the lesion making this case very unusual.